2013
DOI: 10.1007/978-3-642-39206-1_28
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Edge-Disjoint Paths in k-Sums of Graphs

Abstract: We consider the approximability of the maximum edge-disjoint paths problem (MEDP) in undirected graphs, and in particular, the integrality gap of the natural multicommodity flow based relaxation for it. The integrality gap is known to be Ω( √ n) even for planar graphs [14] due to a simple topological obstruction and a major focus, following earlier work [17], has been understanding the gap if some constant congestion is allowed. In planar graphs the integrality gap is O(1) with congestion 2 [23, 7]. In general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…3.1]; see also Proposition 3.3 of Chekuri et al [14]. As a corollary of Theorem 2, we immediately obtain the following proposition about the integrality gap of MaxEDP LP.…”
Section: Multi-commodity Flow Relaxationsupporting
confidence: 56%
See 2 more Smart Citations
“…3.1]; see also Proposition 3.3 of Chekuri et al [14]. As a corollary of Theorem 2, we immediately obtain the following proposition about the integrality gap of MaxEDP LP.…”
Section: Multi-commodity Flow Relaxationsupporting
confidence: 56%
“…Recently, Ene et al [21] showed that MaxEDP admits an O(w 3 )-approximation algorithm on graphs of treewidth at most w. Theirs is the best known approximation ratio in terms of w, improving on an earlier O(w · 3 w )-approximation algorithm due to Chekuri et al [15]. This shows that the problem seems more amenable on "tree-like" graphs.…”
Section: Conjecture 1 [12] the Integrality Gap Of The Standard Multi-mentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition W i already guarantees that S i has the α BW -bandwidth property. If S i is not a good router, then it must be impossible to send large amounts of flow from S i to T in G. In this case, using known techniques (see appendix of [CNS13]), we can show that we can delete an edge from G[S i ], while preserving the 1-well-linkedness of the terminals 6 , contradicting the minimality of G. Therefore, if W i contains at least one large cluster, then it contains a good router. Assume now that all clusters in W i are small.…”
Section: Non-constructive Proofmentioning
confidence: 99%
“…that the paths in P(C) are internally disjoint from C ∪ T . The following lemma can be seen as a variation of the Deletable Edge Lemma of Chekuri, Khanna and Shepherd [5] (the proof of their original lemma can be found in [9]), though it is somewhat simpler. The proof is omitted from this extended abstract.…”
Section: Splitting a Clustermentioning
confidence: 98%